Over half of threatened species require targeted recovery actions to avert human‐induced extinction. Issue 2 (18th July 2022) - Bolam, Friederike C; Ahumada, Jorge; Akçakaya, H Reşit; Brooks, Thomas M; Elliott, Wendy; Hoban, Sean; Mair, Louise; Mallon, David; McGowan, Philip JK; Raimondo, Domitilla; Rodríguez, Jon Paul; Roe, Dilys; et al.
Abstract : Averting human‐induced extinctions will require strong policy commitments that comprehensively address threats to species. A new Global Biodiversity Framework is currently being negotiated by the world's governments through the Convention on Biological Diversity. Here we explored how the suggested targets in this framework could contribute to reducing threats to threatened vertebrates, invertebrates, and plants, and assessed the importance of a proposed target to implement recovery actions for threatened species. Although many of the targets benefit species, we found that extinction risk for over half (57%) of threatened species would not be reduced sufficiently without a target promoting recovery actions, including ex situ conservation, reintroductions, and other species‐specific interventions. A median of 54 threatened species per country require such actions, and most countries of the world hold such species. Preventing future human‐induced extinctions requires policy commitments to implement targeted recovery actions for threatened species in addition to broader efforts to mitigate threats, underpinned by transformative change.